Penentuan Daya Jerap Karbon Aktif Dari Tempurung Kelapa Terhadap Ion Cu(II) - Rispiandi, Fadli; Yusnimar, Yusnimar; Helianty, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Activated carbon which has a high adsorption capacity for the adsorbate. Activated carboncan be produced from materials containing carbon or charcoal was treated in a certain wayto gain more surface area. The research goal was to process coconut shell into a activatedcarbon and determine the adsorption power of the ion Cu (II). The dried coconut shell wascarbonated in a sealed drum to produced charcoal / carbon. Charcoal was crushed into aparticle size of 100 mesh. Charcoals with a size of 100 mesh were activated physically andchemically. The activation process of carbon physically carried out at a temperature of 300,500 and 700 ºC. While chemically, activated carbon was done by used Na2CO3 as anactivator. Carbon/charcoal was soaked in a solution of Na2CO3 for 24 hours. Furthermore, itwas separated from the solution of Na2CO3 and dried at a temperature of 105 ºC. Activatedcarbon obtained both physically and chemically characterized to determine such as ashcontent, moisture content and adsorption power of the iodine solution and Cu(II) in solution. The results showed that the carbon which activation under a temperature of 700 ºC was the best activated carbon has a water content of 4.13%, ash content of 5.25%, iodine number 1262.95% and the adsorption power of the ion Cu(II) 99.96%Keywords : Activated Carbon, Adsorption, Chemical Activation, Coconut Shell and PhysicsActivation